Implications of Small Ruminant Farmers' Socio-Economic Characteristics for Extension Services in South Western Nigeria (1998)
"Farmers' perception of innovation are deeply rooted in the socio-economic structure of existing social systems. Adoption studies have shown that the farmer would not adopt a new practice unless it is compatible with their socio- economic characteristics. This paper highlights some implications for extension services to livestock farmers taking into cognisance the socio-economic characteristics. Two hundred and eighty farmers were selected from the seven states of South Western Nigeria using the large sample size technique (n≥30). Data were collected on the socio-economic characteristics of fanners and their production activities on small ruminant animals. The data collected was subjected to frequency counts and percentages."